Compound Heterozygous CHAT Gene Mutations of a Large Deletion and a Missense Variant in a Chinese Patient With Severe Congenital Myasthenic Syndrome With Episodic Apnea - Liu, Zhimei; Zhang, Li; Shen, Danmin; Ding, Changhong; Yang, Xinying; Zhang, Weihua; Li, Jiuwei; Deng, Jie; Gong, Shuai; Liu, Jun; Qian, Suyun; Fang, Fang (Frontiers in Pharmacology, 2019)
Congenital myasthenic syndromes (CMSs) are a group of inherited disorders caused by genetic defects in neuromuscular junctions. Mutations in CHAT, encoding choline acetyltransferase, cause congenital myasthenic syndrome with episodic apnea (CMS-EA), a rare autosomal recessive disease characterized by respiratory insufficiency with cyanosis and apnea after infections, fever, vomiting or excitement. To date, no studies have reported deletions comprised of multiple exons. Here, using next generation sequencing, we identified compound heterozygous mutations, namely a large maternally inherited deletion, including exons 4, 5, and 6, and a paternally inherited missense variant (c.914T>C [p.Ile305Thr]) in CHAT in a Chinese patient with a severe phenotype of CMS-EA. Furthermore, the large deletion was also validated by real-time fluorescence quantitative polymerase chain reaction. The patient was a 10-month-old boy, who presented with a weak cry and feeding difficulties soon after birth, ptosis at 4 months old, episodic apnea after fever at 9 months old, and respiratory insufficiency with cyanosis and apnea that required intubation after a respiratory tract infection at 10 months old. Unfortunately, he died in the Pediatric Intensive Care Unit soon after hospitalization. The patient’s elder sister had similar clinical manifestations, and she died prior to the age of 2 months old without a diagnosis. Genotype-phenotype correlation analysis revealed that loss-of-function mutations in exons 4-6 of CHAT might cause more severe CMS-EA. To our knowledge, this is the first study to show compound heterozygous CHAT mutations consisting of a large deletion and missense mutation in a patient with CMS-EA.